2019
DOI: 10.9734/ajsspn/2019/v5i130055
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Mixture of Water from Cooked Bean and Human Urine on the Growth of Some Common Plants in Cameroon: Case Study of Talinum fruticosum L. and Ocimum gratissimum L.

Abstract: The sustainable improvement of plant nutrition can provide sufficient food for all and can keep the environment clean. In that point of view, the present study aims to provide to farmers some contextualized and efficient fertilizers. In the present work, 161 plants of Talinum fruticosum L. and 161 plants of Ocimum gratissimum L. were regularly treated with a mixture of human urine and water from cooked beans (Phaseolus vulgaris) in a 1:1 ratio during three months. 161 of each of these plants were used as contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The interaction of bio stimulant and micronutrients application also revealed that the combined application of panchakaviya (3%), humic acid (2%) and ZnSO 4 0.5% + Fe SO 4 0.5% + Mg SO 4 0.5%+ Boric acid 0.3%+Cu SO 4 0.1%+Mo 0.02% (T6) had higher values for fruit length (12.00 cm and 12.00 cm) and fruit diameter (13.00 cm and 12.25 cm) compared with control (T7) (9.17 cm and 9.69 cm). This might be due to the faster absorption of nitrogen present in panchakaviya and micronutrients through cuticle of leaves which increased the plant photosynthetic assimilates [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of bio stimulant and micronutrients application also revealed that the combined application of panchakaviya (3%), humic acid (2%) and ZnSO 4 0.5% + Fe SO 4 0.5% + Mg SO 4 0.5%+ Boric acid 0.3%+Cu SO 4 0.1%+Mo 0.02% (T6) had higher values for fruit length (12.00 cm and 12.00 cm) and fruit diameter (13.00 cm and 12.25 cm) compared with control (T7) (9.17 cm and 9.69 cm). This might be due to the faster absorption of nitrogen present in panchakaviya and micronutrients through cuticle of leaves which increased the plant photosynthetic assimilates [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Cuttings made from young shoots (10-15 cm) can be planted directly in field. Stem cuttings of 1 cm of circumference and 10 cm of length was utilized for planting by Fopoussi Tuebue et al (2019). Okechukwu et al (2014) tested different plant spacing and manuring in field and found that closer spacing of 25  10 cm and application of manure @ 30 t ha -1 yielded higher.…”
Section: Propagationmentioning
confidence: 99%
“…Fopoussi Tuebue et al (2019) informed that growth of waterleaf is higher in fertilized soils than in the unfertilized soils. Bhavithra et al (2019) harvested 1.6 kg of fresh leaf yield per plot at 30 days after planting which was relatively higher than many other leafy vegetables tested.…”
Section: Propagationmentioning
confidence: 99%